The Icelandic Folktales about Magician-Priests: Origins and Significance in the Culture - Solovyeva, Anna, 1991- (2014)
In the middle of the XIX century Jón Árnason collected, carefully categorized and published a monumental collection of Icelandic folktales. One of the big classes of stories included in this collection was devoted to priests and bishops who practiced magic and dealt with all sorts of supernatural creatures. These characters usually have historical counterparts, who once lived and preached in different regions of Iceland. But the imagination of the folk enriched their lives with numerous funny, dangerous and exciting supernatural episodes and endowed the actual priests with many wondrous qualities, among which the overwhelming thirst for knowledge and the quickness and flexibility of mind must be named. The aim of this paper is to show how all the magician-priests are united by their knowledge quest, their guile and their peculiar attitude to life and to moral laws. It is also an attempt to trace various sources and influences that impacted the formation of this type of plot, primarily the mythological Odinnic tradition about supernatural knowledge and the European legends about clerics practicing magic. Besides, the folktales about magician-priests are viewed in the context of the folktale corpus as a whole and of the Icelandic nationalism of the past two centuries. The main idea of the research is that the particular type of folktales is characteristic not only of the literary folktale world, but of the Icelandic world-view and values as they had been reconstructed by the learned nationalists. In this context the quick-minded, guileful and benevolent magician-priest might be seen as an Icelandic ideal of a self-made and practically invincible man. He lives in harmony with his wondrous country and by virtue of his talents manages to balance between good and evil, natural and supernatural, always getting what he wants, never having to pay too dearly.